Pengelolaan Dana Desa untuk Pemberdayaan Masyarakat dalam Meningkatkan Kesejahteraan - Nasendi, Yan Maurid; Toroby, Renida J.; Raharjo, Djoko (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the influence of ADD management and obstacles to managing village funds in Kobakma Village. The method used in this research is qualitative and designed to be descriptive. The data collection technique used by researchers in this research was through interviews and documentation notes. Data analysis techniques start with data reduction, data presentation, and conclusions. The results of the study prove that the management of Village Funds for community empowerment in improving welfare in Kobakma Village, Kobakma District, Central Mamberamo Regency, in the empowerment program has not been optimal even though it has complied with the procedures set out in Perbu No. 5 of 2001. Meanwhile, obstacles have become distortions in the management of village funds for community empowerment in improving welfare in Kobakma Village, Kobakma District, Central Mamberamo Regency; the distance between villages is far, transportation is still on foot, the cost of building materials is high and human resources are still minimal. Keywords: Community Empowerment, Village Fund Management, Improving welfare